Oxygen-Releasing Biomaterials: Current Challenges and Future Applications. Issue 11 (November 2021) - Willemen, Niels G.A.; Hassan, Shabir; Gurian, Melvin; Li, Jinghang; Allijn, Iris E.; Shin, Su Ryon; Leijten, Jeroen
Abstract : Oxygen is essential for the survival, function, and fate of mammalian cells. Oxygen tension controls cellular behaviour via metabolic programming, which in turn controls tissue regeneration, stem cell differentiation, drug metabolism, and numerous pathologies. Thus, oxygen-releasing biomaterials represent a novel and unique strategy to gain control over a variety of in vivo processes. Consequently, numerous oxygen-generating or carrying materials have been developed in recent years, which offer innovative solutions in the field of drug efficiency, regenerative medicine, and engineered living systems. In this review, we discuss the latest trends, highlight current challenges and solutions, and provide a future perspective on the field of oxygen-releasing materials. Highlights: Oxygen tension is a crucial factor in many diseases, and gaining control over local partial pressure of oxygen (pO2 ) using oxygen-releasing materials can have a significant role in overcoming these pathological conditions. Novel oxygen-releasing strategies have extended the oxygen-generating window from several hours to several weeks and offer improved control over oxygen-release profiles by shifting away from pO2 -based diffusion towards biomaterial-controlled oxygen release. Oxygen-releasing biomaterials hold potential to improve many (novel) biomedical areas, including improving in vivo survival of living implants, offering metabolic control over cell fate and tissue function, enhancing the effectivity of photodynamic anticancer therapies, reducing reactive oxygen species-mediated cellular damage, and acting as synthetic red blood cells (RBCs) for in vivo blood oxygenation.